Income Risk and the Decision on Onion Farming - Hindarti, Sri; Rohmatul Maula, Lia; Khoiriyah, Nikmatul (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 1 (2021): Vol.15, No.1, 2021, 2021)
The onion cultivation often faced various risks caused by many factors, so farmers need to make the right decision to start onion cultivation by paying attention to these risks. Therefore, this research was conducted with the aim of 1) analyzing the income risk faced by farmers in developing onion farming, 2) knowing the factors that affect the farming risk, 3) knowing the factors that influence farmers' decisions in planting onion. The research was conducted in Purworejo Village for 4 months with 30 onion farmers as the sample. To analyze the income risk faced by farmers in developing onion farming, it was done by calculating the coefficient of variation (CV). Minimum income was calculated by the residual formula of the squared income function and to determine the factors that influence farming income and farmers' decisions in planting onion, multiple linear regression analysis was performed. The research showed that the risk of onion farming income was quite high, reached 79.72% and the factors that influence were land area, total production, selling price, and production costs. Meanwhile, the factors that influence the decision making of onion farmers were education, age, and farmer experience.